Efficient light trapping of quasi-inverted nanopyramids in ultrathin c-Si through a cost-effective wet chemical method. Issue 99 (11th October 2016) - Tang, Quntao; Shen, Honglie; Gao, Kai; Yao, Hanyu; Jiang, Ye; Zheng, Chaofan; Pu, Tian; Li, Yufang; Liu, Youwen; Zhang, Lei
Abstract : Double-sided quasi-inverted nanopyramids (QIP) is proposed to realize an over 4.2-fold reduction in silicon material usage with the average absorptance value almost the same. Abstract : In this paper, we report quasi-inverted nanopyramids (QIP) for light-trapping in ultrathin c-Si by a cost-effective wet chemical method. The QIP is fabricated by a well-known two-step Ag assisted chemical etching method followed by a post nanostructure rebuilding (NSR) process, lowering the surface area to ∼3.0 times for suppressing surface recombination losses. The comparable average absorptance value of 43 μm c-Si with double-sided QIP to that of 182 μm c-Si with double-sided conventional pyramid in the spectral range of 300–1100 nm demonstrates an over 4.2-fold reduction in material usage. Finally, a simulation model is proposed to explain the superiority of our QIP compared with the periodic inverted pyramid (IP) structure of the same size, presenting a promising method to the mass production of high-efficiency ultrathin c-Si HIT solar cells.